Membongkar Wacana Syariat Islam, Anti Demokrasi Komunitas Fundamentalisme Islam - , Rohmad Suryadi; , Prof. Susetyawan, MA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Discourse application of Islamic Sharia in having state life again find a new expression space post-reformation which accomodate ideology openness. Islamic Sharia Discourse, anti-democracy colors ideal state form discourse which is constructed by two Islamic fundamentalism comunity in which Jama'ah Anshorut Tauhid (JAT) which carries the discourse of Islamic Sharia application through extra-parliamentary politics struggle. And also Hizbut-Tahrir Indonesia which discourse upon Islamic caliphate application to establish a global Islamic state system. Establishment discourse is recently done through a new media in the form of website using internet network. This is directly proportional to the inclination of Indonesian people who start to consume more internet media in searching information needs. This study uses critical discourse analysis methods with techniques of collecting data through articles analysis on discourse of Islamic Sharia, anti-democracy in both of the community website media besides the in-depth interviews, Focus Group Discussion (FGD) and literature study deal with discourse developed by Islamic fundamentalism comunity under study. The theory used in analysis is the theory of critical discourse analysis by Norman Fairclough, discourse and power relations theory by Michel Foucault and The theory of representation by Stuart Hall. So this study can provide a complete overview about the deconstruction of discourse meaning related to Islamic fundamentalism community views on Islamic Sharia and resistance against democracy. The results of study show the discourse on Islamic sharia, anti-democratic of Islamic fundamentalism communities through the construction of religious symbols for political purposes. The Tendency to interpret The Holy book scripture textually and scripturally regardless of social and historical context of the text emergence and also shows discontinuity and inconsistency within the practice. Therefore, the construction of Islamic fundamentalism dicourse text is dominantly as a tool to show the existency of politics rather than religious values to form a expected society according to the guidance of the holy book.